Pendidikan Karakter dalam Pandangan KH. Akhmad Rifa’i - Mu'tamar, Mu'tamar; Djamil, Abdul; Nurcholis, Nanang (Jurnal Studi Islam dan Kemuhammadiyahan (JASIKA), 2024)
The impact of technological developments in the era of globalization is extraordinary. A clear example is in children's education, where children's activities are not well controlled and children often commit crimes and other bad acts. From this we can understand that the implementation of character education in the era of globalization is very important in forming good children's character. This research aims to examine in detail the theory of character education in the view of KH. Ahmad Rifa'i. This research method uses a qualitative descriptive approach which aims to obtain theories about character education according to KH. Ahmad Rifa'i. The primary sources in this research are several tarajumah books by KH. Ahmad Rifa'i. Meanwhile, secondary sources are books related to this discussion, such as articles, magazines and other literature. According to KH Ahmad Rifa'i, character education can be done through cleansing the heart through worship, habituation and training in forming commendable morals/people with character. To create a person with character, a person must practice the qualities of pinuji wolu, which include: asceticism, qonaah, tawakal, patience, mujahadah, blessing, gratitude and sincerity. The aim is to bring peace of mind, which is obtained because of the attitudes and inner activities that have become a person's character and personality, such as gratitude, sincerity, blessing, qonaah and so on. There are also things that are obtained through struggle and hard work, such as patience in riyadloh and mujahadah against lust.